2020
DOI: 10.1002/ange.202012329
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Atomically Dispersed FeN4 Active Sites for CO2 Electroreduction

Abstract: Atomically dispersed FeN4 active sites have exhibited exceptional catalytic activity and selectivity for the electrochemical CO2 reduction reaction (CO2RR) to CO. However, the understanding behind the intrinsic and morphological factors contributing to the catalytic properties of FeN4 sites is still lacking. By using a Fe‐N‐C model catalyst derived from the ZIF‐8, we deconvoluted three key morphological and structural elements of FeN4 sites, including particle sizes of catalysts, Fe content, and Fe−N bond stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 65 publications
(188 reference statements)
2
21
0
Order By: Relevance
“…The ECRR-to-CO includes two steps of electron transfer and one step of CO desorption from the active sites: (1) CO 2 + * + H + + e – → *COOH; (2) *COOH + H + + e – → *CO + H 2 O; (3) desorption of CO, *CO → CO + *. Although the formation of *COOH suffers from large energy barriers, the desorption of the reduced product CO from the active sites is generally the rate-determining step for ECRR-to-CO. Therefore, one of the most critical bottlenecks in ECRR-to-CO is to weaken the binding of *CO on active sites, thus reducing the free energy of CO desorption. In this regard, the key for promotion of ECRR-to-CO conversion efficiency lies in the optimization of the binding strength of the key intermediate *CO and the enhancement of the desorption process of CO …”
mentioning
confidence: 99%
“…The ECRR-to-CO includes two steps of electron transfer and one step of CO desorption from the active sites: (1) CO 2 + * + H + + e – → *COOH; (2) *COOH + H + + e – → *CO + H 2 O; (3) desorption of CO, *CO → CO + *. Although the formation of *COOH suffers from large energy barriers, the desorption of the reduced product CO from the active sites is generally the rate-determining step for ECRR-to-CO. Therefore, one of the most critical bottlenecks in ECRR-to-CO is to weaken the binding of *CO on active sites, thus reducing the free energy of CO desorption. In this regard, the key for promotion of ECRR-to-CO conversion efficiency lies in the optimization of the binding strength of the key intermediate *CO and the enhancement of the desorption process of CO …”
mentioning
confidence: 99%
“…A wrinkle configuration of the FeN 4 site was found to kinetically improve the activity for ORR, and thermodynamically promote the activity for CO2RR on Fe−N−C catalysts. 48,49 Motivated by these previous results, we herein computationally examined the effect of compressive strain on the activity and selectivity on FeN 4 and FeN 3 sites for NRR. The atomic models of FeN 4 and FeN 3 sites with compressive strain are shown in Figure 2.…”
Section: Resultsmentioning
confidence: 93%
“…Our previous studies on the oxygen reduction reaction (ORR) and carbon dioxide reduction reaction (CO2RR) on Fe−N−C catalysts have demonstrated that the compressive strain caused by the elevated-temperature treatment has a beneficial effect in facilitating their catalytic activity. 48,49 Herein, we employed the first-principles density functional theory (DFT) to study how the compressive strain in graphene layers would affect the NRR activity and selectivity on both FeN 4 and FeN 3 sites embedded in the graphene layer. Our results suggest that structural distortion could be used to enhance the catalytic properties of metal and nitrogen codoped carbon catalysts for NRR.…”
Section: Introductionmentioning
confidence: 99%
“…The change of P species according to the amount of phosphoric acid added was not obviously observed; however, the content of P was in proportion to the amount of phosphoric acid. Fe 2p spectra were deconvoluted with FeO (709.2 eV), Fe-N/Fe 2 O 3 (711.9 eV), Fe hydroxides (713.8 eV), and satellite peaks (718.9 eV) [67] (Figure 6). Due to the low content of Fe, it was difficult to precisely reveal the electronic state of Fe; this has been reported by previous studies on M-N-C [41,47].…”
Section: Resultsmentioning
confidence: 99%